HUMAN RELIABILITY ANALYSIS OF PACKAGING PRODUCTION OPERATORS WITH HIERARCHICAL TASK ANALYSIS (HTA) AND FUZZY HEART METHODS - Suryapranatha, Dicky; Perdana, Muhammad Fadli; Saputri, Ika Adhityaning (Journal of Industrial Engineering Management, 2025)
Machine operator experienced has a significant number of production defects and frequent failures to meet production targets. These issues are largely attributed to the high level of operator involvement in the production process, increasing the likelihood of human error. To address this, a Human Reliability Analysis (HRA) was conducted to identify factors contributing to human error and the associated risks of production defects. The analysis employed the Hierarchical Task Analysis (HTA) method to break down each task. Subsequently, Human Error Probability (HEP) and the Human Error Assessment and Reduction Technique (HEART) were used to evaluate the likelihood of human error and overall human reliability. In the HEART method, the Assessed Proportion of Effect (APOE) value was determined through expert judgment. To mitigate the subjectivity in APOE determination, a modification using Fuzzy Linguistic Expression was applied.